2021
DOI: 10.1155/2021/2780257
|View full text |Cite
|
Sign up to set email alerts
|

Usability Barriers for Elderly Users in Smartphone App Usage: An Analytical Hierarchical Process-Based Prioritization

Abstract: With the latest technology, smartphone's profound impact may be valuable for the users in different age groups, but the elders always face difficulties while adopting the technology. The usability of a smartphone application is essential when the target audience is elderly users, as the designer did not satisfy the specific requirements. The importance of smartphone application and the issues that the elders are facing in using smartphones have motivated us to provide a list of barriers that could negatively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Thus, if they do not perceive the benefits of using technology, they will not adopt it (Liu et al, 2021). Awan et al (2021) found that elderly people typically face two main types of issues when considering the usage of smartphones. First, as Liu et al (2021) stated, one type of issue consists of age-related issues, such as memory decline, diminished cognitive and physical abilities, and weaker mental models and sensory functions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if they do not perceive the benefits of using technology, they will not adopt it (Liu et al, 2021). Awan et al (2021) found that elderly people typically face two main types of issues when considering the usage of smartphones. First, as Liu et al (2021) stated, one type of issue consists of age-related issues, such as memory decline, diminished cognitive and physical abilities, and weaker mental models and sensory functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, we had a low usage of ZTEx App which might relate to over 90% of our participants were aged 50 years or older. A review identified the top three most common barriers for elderly people using Apps that included (i) small font size, screen size, font type, buttons, color contrast, (ii) lack of experience and knowledge in technology, and (iii) menu with too many options, and navigation ( 45 ). Thus, it is important to consider the needs and requirements of elderly users in the design and development phase of a smartphone application to overcome the potential barriers to App use in future trials.…”
Section: Discussionmentioning
confidence: 99%
“…In general, older people are less aware of the importance of technology. Lack of awareness and ignorance regarding the implementation of this technology can be a barrier when using it (Awan et al, 2021).…”
Section: Levels Of Effectiveness Efficiency and Satisfaction In Using...mentioning
confidence: 99%